PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, ASIMETRI INFORMASI DAN WHISTLEBLOWING TERHADAP PENCEGAHAN KECURANGAN PADA BADAN USAHA MILIK DESA (BUMDes) DI KABUPATEN SUKABUMI - Setiawan, Ade Budi; Aulia, Uan; Hutomo, Yoyok Priyo (Jurnal Akuntansi Kompetif, 2025)
The purpose of this research is to determine the influence of human resource competence (HR), information asymmetry, and whistleblowing on fraud prevention in Village-Owned Enterprises (BUMDes) in Sukabumi Regency. The research population consists of 147 BUMDes managers. The sampling technique employed probability sampling with a simple random sampling method, resulting in 60 respondents who met the research criteria. Using a quantitative approach with a survey method, data was collected from BUMDes manager respondents. Multiple linear regression analysis with the assistance of SPSS version 26 software was used to determine the influence of independent variables on fraud prevention. The research findings indicate that simultaneously, HR competence, information asymmetry, and whistleblowing have a positive and significant influence on fraud prevention. Partially, HR competence and whistleblowing have a positive and significant influence, while information asymmetry has no influence and is not significant in preventing fraud. The contribution of these three variables to fraud prevention is 75.3%, while the rest is influenced by other factors not discussed in this study. Therefore, increasing HR competence and implementing effective whistleblowing are highly recommended to maximize fraud prevention in BUMDes.